Cation-exchange resins as heterogeneous catalysts for the synthesis of 1,3-butadiene from propylene and formaldehyde - T. M. Kutuzova; O. M. Kuznetzova; R. A. Akhmedyanova (Chimica Techno Acta)
The possibility of using the cation-exchange resin Lewatit K2420 as a catalyst for the synthesis of 1,3-butadiene from isopropyl alcohol and formaldehyde solution in one technological stage has been shown. The regularities of the process have been established and the influence of the formaldehyde form (a cyclic trimer 1,3,5-trioxane and a 37% solution in water) on the composition of the reaction mass and the yield of the main and by-products has been assessed. It has been shown that the Lewatit K2420 heterogeneous catalyst showed catalytic activity in all reactions occurring in the synthesis of 1,3-butadiene, including the decomposition of 1,3,5-trioxane, dehydration of isopropyl alcohol into propylene,  condensation of propylene and formaldehyde, dehydration of 3-butene-1-ol, decomposition of 4-methyl-1,3-dioxane, etc.